A Study of Factors Affecting on Online Shopping Behaviour of Consumers in Meerut Urban Area - Anubha (Journal of Commerce and Trade, 2019)
E-Commerce is exchange of information using network-based technologies. In the present high cost situation, e-Commerce can be used as a competitive strategy. It successfully includes the entire online process of developing, marketing, selling, delivering, servicing and paying for products and services. On-line shopping is a recent phenomenon in the field of E-Business and is definitely going to be the future of shopping in the world. Most of the companies are running their on-line portals to sell their products/services on-line. Though online shopping is very common outside India, its growth in Indian Market, which is a large and strategic consumer market, is still not in line with the global market. The major benefit of online shopping is the ability to 'compare the products and the prices' easily. Instead of running around to several different traditional stores and trying to remember or write down details such as prices and features, the shopper can simply open two or more browsers to easily compare more than one item. The present research paper has used Qualitative and Quantitative research methods to study the impact of Demographic factors of consumers on on-line shopping parameters like satisfaction with on-line shopping, future purchase intention, frequency of on-line shopping, numbers of items purchased, and overall spend on on-line shopping. The data was collected through Questionnaires from urban area of Meerut district. The results of study reveal that on-line shopping in India is significantly affected by various Socio-Demographic factors. Classification- JEL: O17, P15